2009
DOI: 10.1007/s11596-009-0603-5
|View full text |Cite
|
Sign up to set email alerts
|

Liver-specific reduction of Mfn2 protein by RNAi results in impaired glycometabolism and lipid homeostasis in BALB/c mice

Abstract: Mitofusin-2 (Mfn2) gene expression is positively correlated with insulin sensitivity in patients with type 2 diabetes. However, it is unclear if Mfn2 is involved in carbohydrate metabolism and lipid homeostasis. In order to investigate the specific functions of Mfn2 in glycometabolism and lipid homeostasis in BALB/c mice, a RNA interference technique-mediated hydrodynamic injection was developed, in which short hairpin RNAs (shRNAs) were used to inhibit the Mfn2 expression in vivo. Seventy-two mice were random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Compared to Mfn1, Mfn2 is independent of its role as a mitofusin, and it can also trigger mitochondrial energization by regulating OXPHOS expression [50]. Mfn2 reduction decreased the rate of fatty acid synthesis in the liver, and the Mfn2/shRNA mice exhibited hypertriglyceridema, suggesting that Mfn2 played an important role in maintaining glucose and lipid homeostasis [51]. Repression of Mfn2 reduced glucose oxidation, mitochondrial membrane potential, cell respiration, and mitochondrial proton leak and reduced Mfn2 expression may explain some of the metabolic alterations associated with obesity [52].…”
Section: Discussionmentioning
confidence: 99%
“…Compared to Mfn1, Mfn2 is independent of its role as a mitofusin, and it can also trigger mitochondrial energization by regulating OXPHOS expression [50]. Mfn2 reduction decreased the rate of fatty acid synthesis in the liver, and the Mfn2/shRNA mice exhibited hypertriglyceridema, suggesting that Mfn2 played an important role in maintaining glucose and lipid homeostasis [51]. Repression of Mfn2 reduced glucose oxidation, mitochondrial membrane potential, cell respiration, and mitochondrial proton leak and reduced Mfn2 expression may explain some of the metabolic alterations associated with obesity [52].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies showed that MFN2 knockdown promoted neural ectodermal differentiation of hESCs [ 8 ]. Several studies have shown that it also plays an important role in mitochondrial metabolism and function, mainly manifested in the effect on glucose oxidation and cellular respiration [ 9 ]. Studies have shown that the lack of MFN2 inhibits the expression of OXPHOS complexes, and its participation in mitochondrial metabolism is independent of mitochondrial fusion [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…A key effector appears to be mitofusin-2 (Mfn2), a mitochondrial fusion protein anchored to the outer mitochondrial membrane that participates in maintaining the mitochondrial morphology and function (14). Several studies have identified that Mfn2 is reduced in the liver and skeletal muscle of diabetic animals (15,16). Mfn2 is regulated through different pathways including phosphatidylinositol 3-kinase (Pi3k)/RAC-alpha serine/threonineprotein kinase (Akt) signaling, and it and may be beneficial to glucose and lipid homeostasis in T2DM (17,18).…”
mentioning
confidence: 99%